Nasopharyngeal Carriage in Children After the Introduction of Generalized Infant Pneumococcal Conjugate Vaccine Immunization in Germany - Rose, Markus A.; Laurenz, Maren; Sprenger, Ralf; Imöhl, Matthias; van der Linden, Mark (Frontiers in Medicine, 2021)
Epidemiological data on nasopharyngeal (NP) bacterial carriage in children in Germany are scarce. We prospectively characterized NP colonization to evaluate the impact of pneumococcal immunization. We longitudinally collected NP swabs from two-month-old infants (visit 1; V1) at eight representative pediatric offices 10/2008-06/2009. The second swabs were taken at age 9-12 months (V2); the third swab was taken 3-6 months after the booster vaccination at age 17-19 months (V3), and the fourth swab (V4) at age 59-61 months. Samples were broth enriched, cultured for bacteria, and isolates were serotyped. Demographic risk factors for colonization were evaluated. Among 242 vaccinees, bacterial NP carriage increased with age (from 27.2% [V1] to 70.1% [V4]); leading isolates were S. pneumoniae, H. influenzae, M. catarrhalis, and S. pyogenes. Overall pneumococcal carriage increased (14.7% [V1], 31.5% [V2], 34.8% [V3], 42.2% [V4]), being even greater among day-care attendees. Serotype distribution changed during the study period, with vaccine serotypes declining. At visit 4, 10-valent pneumococcal conjugate vaccine (PCV10) serotypes were no longer among the NP flora, while some serotypes unique to 13-valent pneumococcal conjugate vaccine (PCV13; 3 and 19A) were found. In Germany, universal infant PCV immunization was associated with an almost complete eradication of PCV-serotypes and concomitant increase of non-PCV-serotypes, mainly 11A, 22F, and 23A.